Evolving a mitigation of the stress response pathway to change the basic chemistry of life - Tolle, Isabella; Oehm, Stefan; Hoesl, Michael Georg; Treiber-Kleinke, Christin; Peil, Lauri; Bozukova, Mihaela; Albers, Suki; Adamu Bukari, Abdul-Rahman; Semmler, Torsten; Rappsilber, Juri; Ignatova, Zoya; Gerstein, Aleeza C.; et al. (Frontiers in Synthetic Biology, 2023)
Despite billions of years of evolution, there have been only minor changes in the number and types of proteinogenic amino acids and the standard genetic code with codon assignments across the three domains of life. The rigidity of the genetic code sets it apart from other aspects of organismal evolution, giving rise to key questions about its origins and the constraints it places on innovation in translation. Through adaptive laboratory evolution (ALE) in Escherichia coli, we aimed to replace tryptophan (Trp) in the genetic code with an analogue L-β-(thieno[3,2-b]pyrrolyl)alanine ([3,2]Tpa). This required Escherichia coli to recruit thienopyrrole instead of indole and allowed reassignment of UGG codons. Crossing the stress response system emerged as a major obstacle for ancestral growth in the presence of [3,2]Tp and Trp limitation. During ALE, a pivotal innovation was the deactivation of the master regulon RpoS, which allowed growth solely in the presence of [3,2]Tp in minimal medium. Notably, knocking out the rpoS gene in the ancestral strain also facilitated growth on [3,2]Tp. Our findings suggest that regulatory constraints, not just a rigid translation mechanism, guard Life's canonical amino acid repertoire. This knowledge will not only facilitate the design of more effective synthetic amino acid incorporation systems but may also shed light on a general biological mechanism trapping organismal configurations in a status quo.